Genetic susceptibility to coronary artery disease: from promise to progress. - Watkins, H; Farrall, M (2006)
Family history is an important independent risk factor for coronary artery disease (CAD), and identification of susceptibility genes for this common, complex disease is a vital goal. Although there has been considerable success in identifying genetic variants that influence well-known risk factors, such as cholesterol levels, progress in unearthing novel CAD genes has been slow. However, advances are now being made through the application of large-scale, systematic, genome-wide approaches. Recent findings particularly highlight the link between CAD and inflammation and immunity, and highlight the biological insights to be gained from a genetic understanding of the world's biggest killer.